Implementing exercise and self-management for women with breast cancer during treatment: results of the NEXT-BRCA randomized controlled trial - Jenna Smith-Turchyn; Derek W. Stouth; Joshua A. J. Keogh; Elizabeth Ball; Myanca Rodrigues; Julie Richardson; Louise Bordeleau; Sarah Neil-Sztramko; Oren Levine; Lehana Thabane; Catherine M. Sabiston; Som D. Mukherjee (Scientific Reports)
Abstract The purpose of this study was to determine the feasibility (recruitment, retention, and adherence rates) and effectiveness of institution-based exercise and self-management (SM) on physical activity (PA) level, exercise knowledge and intention, health status, functional capacity, patient engagement, and lower extremity strength for individuals with breast cancer receiving treatment. We conducted a hybrid implementation-effectiveness trial (type 1), including female participants with a current diagnosis of breast cancer undergoing treatment. Participants were randomized to (1) exercise and SM (EXSM; 8 in person exercise sessions and SM education), (2) SM only (8 sessions of SM), or (3) usual care (UC; no intervention). The RE-AIM model was used to explore the interventions success. The primary outcome was PA level at post-intervention. An ANCOVA determined effectiveness of the intervention at each timepoint. Eighty-five participants were included in the study. Study recruitment was 72%. Both the EXSM and SM interventions had high levels of retention (EXSM: 72%; SM: 93%) and adherence (EXSM: 76%; SM: 93%). A significant effect of group was found between EXSM and UC for PA level at post-intervention timepoint (adjusted mean difference: 9.28 (95% CI 6.45, 12.10); p < 0.001), and was maintained at 6- and 12-month follow-ups (11.78 (8.93, 14.64); p < 0.001; 11.10 (8.28, 13.92); p < 0.001). Exercise and SM using strategies that maximize availability and accessibility of exercise and SM services for survivors of breast cancer can successfully be implemented during treatment within the cancer institution in Canada. Future research should explore implementation of this program at multiple centers, maximizing referral of diverse participants from diverse providers, and consider cost-effectiveness of the interventions provided over the long term in order to facilitate sustained implementation across cancer centers.